The sixth man - Baldacci, David (New York : Grand Central Pub., 2011)
After alleged serial killer Edgar Roy is locked away in a psychiatric unit, private investigators Sean King and Michelle Maxwell are called in by Roy's lawyer to look into the case.
A sequel to the author's First family.
Keywords: Serial murder investigation -- Fiction; Psychiatric hospital patients -- Fiction; Private investigators -- Fiction. LOCATION CALL NO. STATUS APL Fiction FIC Baldacci, D. c.2 AVAILABLE APL Fiction FIC Baldacci, D. c.3 AVAILABLE Bailey Fiction BALDACCI AVAILABLE Baxter ML Adult Fiction F Bal DUE 07-30-13 Baxter ML Adult Fiction F Bal AVAILABLE Belfast General Fiction FIC BAL AVAILABLE Boothbay Hbr Fiction FIC BAL AVAILABLE Calais Free Lib Fiction B175 sm AVAILABLE Camden PL Fiction F Bal AVAILABLE CML Adult Fiction FIC Baldacci David six AVAILABLE